Social Media Marketing And Financial Performance Of Tour Firms In Kigezi Uganda - agaba, Moses; Moses, Agaba (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Purpose - This study examines the impact of gender inequality on socio-economic development in Nigeria, focusing on cultural and religious beliefs, education, employment, healthcare, and political participation. Methodology/approach - Using a mixed-methods approach, the research collected quantitative data from 394 respondents across Northern Nigeria, supplemented by qualitative insights from key informants. Descriptive and inferential statistical analyses, including correlation and regression tests, were conducted using SPSS to assess the relationship between gender disparities and development indicators. Findings - The findings reveal that cultural and religious norms significantly restrict women’s roles, with a strong positive correlation (r = 0.46, p < 0.001) between patriarchal beliefs and hindered economic progress. Gender inequality in education (r = 0.42) and employment (r = 0.38) further exacerbates underdevelopment by limiting female participation in productive sectors. Healthcare disparities (r = 0.40) negatively affect maternal health and workforce productivity, while political marginalization of women (r = 0.29) reduces inclusive governance and policy responsiveness. The study concludes that systemic gender inequality impedes Nigeria’s socio-economic advancement. Novelty/value – This study provide a solid foundation for a framework that would enhance socio-economic development in Nigeria through gender inequality using survey.